2021
DOI: 10.33400/kuje.913349
|View full text |Cite
|
Sign up to set email alerts
|

Question types in the T.R. history of revolution and Kemalism textbooks in terms of historical understanding

Abstract: Tarihsel anlama açısından T.C. İnkılap Tarihi ve Atatürkçülük ders kitaplarında yer alan soru tipleri ÖZGeçmişteki bir konu üzerine öğrencilerin birer tarihçi gibi problem çözme süreci olarak tanımlayabileceğimiz tarihsel anlamanın öğrencilerde gerçekleşebilmesini kolaylaştırmak için, ders kitabındaki ilgili konu ve dönem üzerine uygun soru sorma, hem kanıtın orijinalliğinin tespiti hem de analizinde kilit rol oynamaktadır. Bu çalışma ile T.C. İnkılap Tarihi ve Atatürkçülük ders kitabında yer alan sorular ile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…This means that knowledge (including listening and reading) must be integrated with existing schema and cognitive frameworks to answer questions. In parallel studies, it was found that the questions in secondary school and high school textbooks mostly correspond to low-level cognitive levels and are not suitable for the creation step; that is, it was determined that it measures the ability to remember facts, events and/or people with expressions used in the lesson (Akhan & Öztürk, 2021;Candeğer, 2016;Kaptan-İzmir & Topçu, 2021;Mindivanlı Akdoğan & Ceylan, 2021;Oran & Karalı, 2019;Shara, 2020;Sholikah, 2021;Tayyeh et al, 2021). An important question to be answered in the light of the results is why the learning outcomes and questions differ in terms of cognitive levels.…”
Section: Resultsmentioning
confidence: 99%
“…This means that knowledge (including listening and reading) must be integrated with existing schema and cognitive frameworks to answer questions. In parallel studies, it was found that the questions in secondary school and high school textbooks mostly correspond to low-level cognitive levels and are not suitable for the creation step; that is, it was determined that it measures the ability to remember facts, events and/or people with expressions used in the lesson (Akhan & Öztürk, 2021;Candeğer, 2016;Kaptan-İzmir & Topçu, 2021;Mindivanlı Akdoğan & Ceylan, 2021;Oran & Karalı, 2019;Shara, 2020;Sholikah, 2021;Tayyeh et al, 2021). An important question to be answered in the light of the results is why the learning outcomes and questions differ in terms of cognitive levels.…”
Section: Resultsmentioning
confidence: 99%